An evaluation of a community-based intervention in England aiming to reduce inequalities in exercise participation - Jane Wills; Katya N. Mileva; Susie Sykes; Charles Graham; Chris Flood; Catherine L. Jenkins; Jessica Owugha; Terassa Taylor-Kaveney (Frontiers in Sports and Active Living)
IntroductionExercise referral schemes are a common intervention that seek to address physical inactivity. There is limited evidence on whether they can address the inequalities in inactivity associated with income, age, and gender. A novel intervention that sought to address barriers to the uptake of physical activity schemes including access, cost, and specific health and social needs of participants was evaluated in a mixed methods study.MethodsSerial qualitative interviews with participants were conducted across three time points over the six-month intervention and the routine outcome data collected by the delivery partner were statistically analysed after stratification for referral route, demographic and socioeconomic status and engagement. Data from non-participants in the intervention from the targeted community were collected through street intercept surveys. A descriptive cost analysis was undertaken to understand the cost of delivery.Results and discussionThe study found small improvements in health outcomes and engagement. The novel features of the intervention that aimed to address inequalities in the uptake of physical activity—personalised programme, extended time offer, free and subsidised offer, a dedicated health coach—all succeeded in acting as enablers to uptake although very few individuals met the recommended frequency for attendance.